A study of the nature and distribution of membrane bound protein kinase in various tissues with particular reference to brain - Carstens, Machteld Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical biochemistry)) - University of Stellenbosch, 1977.